Starting out with C++ from control structures through objects - Gaddis, Tony (Pearson Education Limited, 2019)
Starting Out with C++: From Control Structures through Objects covers control structures, functions, arrays, and pointers before objects and classes in Tony Gaddis's hallmark accessible, step-by-step presentation. His books help beginning students understand the important details necessary to become skilled programmers at an introductory level. Gaddis motivates the study of both programming skills and the C++ programming language by presenting all the details needed to understand the "how" and the "why"-but never losing sight of the fact that most beginners struggle with this material. His approach is gradual and highly accessible, ensuring that students understand the logic behind developing high-quality programs. As with all Gaddis texts, clear and easy-to-read code listings, concise and practical real-world examples, and an abundance of exercises appear in every chapter. Updates to the 9th Edition include revised, improved problems throughout and a new chapter featuring completely rewritten and expanded material on the Standard Template Library (STL).